2019
DOI: 10.3390/ijms20081991
|View full text |Cite
|
Sign up to set email alerts
|

Clobetasol Modulates Adult Neural Stem Cell Growth via Canonical Hedgehog Pathway Activation

Abstract: Sonic hedgehog (Shh) signaling is a key pathway within the central nervous system (CNS), during both development and adulthood, and its activation via the 7-transmembrane protein Smoothened (Smo) may promote neuroprotection and restoration during neurodegenerative disorders. Shh signaling may also be activated by selected glucocorticoids such as clobetasol, fluocinonide and fluticasone, which therefore act as Smo agonists and hold potential utility for regenerative medicine. However, despite its potential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…The rate of cell growth (R.C.G.) was calculated as previously described [ 11 ]. Briefly, cells were seeded on six multiwell plates at a final density of 2 × 10 4 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of cell growth (R.C.G.) was calculated as previously described [ 11 ]. Briefly, cells were seeded on six multiwell plates at a final density of 2 × 10 4 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Sonic Hedgehog (SHH) represents one of the most relevant signalling pathways mediating both cell fate and differentiation [ 8 , 9 , 10 ]. The activation of 7-transmembrane protein Smoothened (SMO) determines the GLI-Kruppel family member 1 (GLI1) nuclear translocation promoting proliferation, stem cell renewal and survival [ 10 , 11 , 12 ]. SHH dysregulation has been reported in brain tumors, including GBM [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of each biomarker was assessed by the receiver operating characteristic (ROC) curve analyses [ 86 , 87 ]. Nonparametric ROC curves analyzed AD vs. NDHC.…”
Section: Methodsmentioning
confidence: 99%
“…All these pathways promote bone remodeling, inducing MSC differentiation into mature OBs. Several works have demonstrated that WNT/β-catenin signaling is involved in microenvironmental transformation in PMF [ 125 ]. Moreover, the SHH pathway has been found to be upregulated in PMF, suggesting a potential interplay with WNT/β-catenin in mediating osteosclerotic mechanisms [ 126 ].…”
Section: The Biochemical Network Of Osteosclerosis In Pmfmentioning
confidence: 99%